Escalation of Divorce Suits From Wives Against Husbands From the Perspective of Maqashid Syari'ah Case Study in Lore Utara District, Poso Regency - Talla, Tamrin; Kamaruddin, Kamaruddin; Fatimawali, Fatimawali; Gazali, Gazali (State Islamic University Datokarama Palu, 2024)
The divorce rate in Indonesia continues to increase, as data shows that in 2021, there were 447,743 divorce cases, with 75.34% of them being divorce lawsuits filed by wives. This phenomenon is no exception in North Lore District, Poso Regency, where divorce lawsuits have increased significantly in the last three years. This study aims to analyze the main causes of the escalation of divorce lawsuits by wives against husbands in the area from the perspective of Maqashid Syari'ah. Data shows that domestic conflicts are often triggered by violations of the husband's rights and obligations, domestic violence, and unmanaged differences in character. In addition, the quality of marriage advice, which is still formal, contributes to the weak readiness of couples to face the challenges of marriage. Through a qualitative approach, this study found that the wife's increasing awareness of her rights is a significant factor in filing for divorce. This study emphasizes the importance of improving the quality of marriage advice based on Maqashid Syari'ah to prevent domestic conflict and maintain family integrity.